Motivação da leitura por meio de atividades com textos humorísticos - Gregio, Solange Ana de Macedo (2006)
Annually, lots of avaliation programs like Saresp, Saeb and Enem show that the capacity of interpretation and produce of texts of our students is each more discouraged.The numbers that indicate this results take us to think in our professional reality, once tha t the great problem keep being a short nível of our child s teaching. Belive that a provable motive to indexes to be short find as a matter of the responsables to teach privileging the decodification of the words. To improve this indexes and to help students to like and to firm a engagement with the reading, the teachers need to study and to broadcast to your students different strategys of readings that take them to produce sense in their reading. Our suggestion is to work with different kinds of humoristic texts, because we belive that this can take fun and to take them a significant reading. So, our objectives are: - to contribute to research about readings at the scholar ambient, once that we consider essential to development of the students; - to show the reading motivation through the construction sense, sustain determined strategys cognitive like easy elements, that quality the reader to know what is reading; - to amplify the knowledge of the language by different approach of general textual, and we bealive this approach incluse and amplity the student s perspective in the letters man s word. To attend the objeticves, we use like theoretical support studies from Ângela Kleiman (1989), Eni Orlandi (1988) and Van Dijk (1992) that give importance the reading in the cognitive perspective, affective and social. The work s result can be checked in the criation of differents pedagogic proposal of literature of the humoristic texts, always worked since theorical sedimental chosen. We hop to be contributing to a significative literature